Karakteristik Fisik Ternak Kambing Peranakan Etawa Di Desa Gumelar Kecamatan Gumelar - ilkham Prasetio; Sari Tuswati; Fani Evadewi; Doso Sarwanto (MEDIA PETERNAKAN, 2025)
The research entitled Physical Characteristics of Etawa Crossbred Goats in Gumelar Village, Gumelar District, Banyumas Regency, was conducted on February 9-11, 2025. This study aims to determine the physical characteristics of Etawa Crossbred goats in Gumelar Village, including fur color, rewos fur, facial profile, ear shape, horn shape. The research material used was 106 Etawa Crossbred goats from three Livestock Farmer Groups. The method used in this study was a survey by conducting direct observation of Etawa Crossbred goats in Gumelar Village. Data analysis in this study used descriptive analysis with five parameters, namely fur color, rewos fur, facial profile, ear shape, and horn shape. The results of the study showed that the color of the fur was dominated by black and white (PH), which was 88 percent, most of them had rewos fur, which was 92 percent, the facial profile of all PE goats was convex, the shape of the ears of 100 percent of PE goats was long and drooping, and most of the PE goats had small horns, which was 98 percent